The Embodiment of Bakhtin’s Polyphony in Faulkner’s novel The Sound and The Fury (1929) - BEDJ ,Razika; KORICHI ,Souhila (Faculty of Letters and Foreign Languages Department of English, 2019)
Each literary era claims a unique style and philosophy of literature, to which many authors ascribe. William Faulkner is a well-known American writer whose fiction stands for literary modernism. The present dissertation examines the literary modern experimentation in William Faulkner’s novel The Sound and the Fury (1929). It aims to study the modern narrative techniques employed by Faulkner to achieve this experimentation with polyphony and different narrative devices. More accurately, this research seeks to examine the proper use of polyphony as well as fragmented narration in the studied novel. Mikhail Bakhtin who researches the works of the Russian writer Dostoevsky proposes the theory of polyphony to literature. According to Bakhtin, many independent and unmerged voices and valuable types of consciousnesses in a work compose the true polyphony. This investigation suggests that the use of different modernist techniques serve Faulkner to achieve his goal of presenting a highly modernist novel. Additionally, to better achieve his innovative techniques, Faulkner uses four radically different narrators, each one of them tells the story from his own perspective. Ultimately, the concept of polyphony is employed effectively in Faulkner’s novel The Sound and the Fury.